Determinants of Elevated NT-proBNP Levels in Patients With Hypertrophic Cardiomyopathy: An Echocardiographic Study - MUTLU, BÜLENT (ELSEVIER SCIENCE INC, 2009)
Background: The purpose of this study was to explore the relationship between plasma N-terminal pro-B-type natriuretic peptide (NT-proBNP) and extensive echocardiographic variables in patients with hypertrophic cardiomyopathy (HCM). Methods: We evaluated plasma NT-proBNP levels in 88 patients with HCM and examined the plasma NT-proBNP levels' relationships with echocardiographic indexes. Echocardiographic variables were analysed using univariate and multivariate logistic regression to identify predictors of NT-proBNP elevation. Results: Several echocardiographic variables predicted NT-proBNP elevation, including left atrial dimension index (LADI), left ventricular maximal wall thickness (MWT), left ventricular posterior wall thickness, severe mitral regurgitation, mitral septal and lateral tissue Doppler velocities, and mitral septal E/Ea ratio. Left ventricular ejection fraction, left ventricular dimensions, mitral early flow propagation velocity, isovolumic relaxation time, and left ventricular outflow tract obstruction were not significant predictors of NT-proBNP in this group of patients. With multivariate analysis LADI (HR 5.0; 95% CI 1.5-17.1, p = 0.01) and MWT (HR 4.0; 95% CI 1.2-13.2, p = 0.022) emerged as independent determinants of NT-proBNP elevation. Conclusions: In HCM plasma NT-proBNP is prominently increased. LADI and MWT are independent predictors of elevated levels. These data indicate that NT-proBNP elevations are mainly determined by diastolic load in HCM. (Heart, Lung and Circulation 2009;18:266-270) (c) 2008 Australasian Society of Cardiac and Thoracic Surgeons and the Cardiac Society of Australia and New Zealand. Published by Elsevier Inc. All rights reserved.
Keywords: Hypertrophic cardiomyopathy; NT-proBNP; Left atrium; VENTRICULAR FILLING PRESSURES; NATRIURETIC PEPTIDE LEVELS